Prototipe Alat Pendeteksi Detak Jantung, Saturasi Oksigen, dan Suhu Tubuh Berbasis Arduino Mega Menggunakan Fuzzy Sugeno - Annisa Dwita Aurum; Endah Fitriani (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2024)
Health is a highly sought-after aspect for all living beings on Earth. By health checkups can prevent health disturbances that may develop into diseases. Various health checks include heart rate, oxygen saturation, and body temperature checks. These checks can be conducted independently at home using various health monitoring devices available in the market. However, these health devices only display numerical values without providing detailed information about the results, requiring users to seek further information. With the development technological and sensors, three health parameters can be combined into a single detection device capable of storing results. This detection device is designed using an Arduino Mega microcontroller with the Fuzzy Logic Sugeno classification method. Fuzzy input is obtained from the MAX30102 sensor for heart rate and oxygen saturation, as well as the MLX90614 sensor for body temperature. The detection results are displayed based on their classifications along with recommendations and can be stored on the device using a MicroSD card and sent to a Telegram application. The device operates on batteries for increased practicality.This research an accuracy of 96.11% for the MAX30102 sensor and 98.83% for the MLX90614 sensor. The Fuzzy Sugeno method was successfully implemented in the device and met expectations, producing outputs consistent with calculations. The data storage process using the SDCard Module was successful with a delay of 6.17 seconds, allowing review previous results. The battery testing indicated that the device can operate for up to 4 hours.